Impact on Bacterial Community in Midguts of the Asian Corn Borer Larvae by Transgenic Trichoderma Strain Overexpressing a Heterologous chit42 Gene with Chitin-Binding Domain - Li, Yingying (Public Library of Science, 2013)
This paper is the first report of the impact on the bacterial community in the midgut of the Asian corn borer (Ostrinia furnacalis) by the chitinase from the transgenic Trichoderma strain. In this study, we detected a change of the bacterial community in the midgut of the fourth instar larvae by using a culture-independent method. Results suggested that Proteobacteria and Firmicutes were the most highly represented phyla, being present in all the midgut bacterial communities. The observed species richness was simple, ranging from four to five of all the 16S rRNA clone libraries. When using Trichoderma fermentation liquids as additives, the percentages of the dominant flora in the total bacterial community in larval midgut changed significantly. The community of the genus Ochrobactrum in the midgut decreased significantly when the larvae were fed with the fermentation liquids of the transgenic Trichoderma strain Mc4. However, the Enterococcus community increased and then occupied the vacated niche of the Ochrobactrum members. Furthermore, the Shannon–Wiener (H) and the Simpson (1-D) indexes of the larval midgut bacterial library treated by feeding fermentation liquids of the transgenic Trichoderma strain Mc4 was the lowest compared with the culture medium, fermentation liquids of the wild type strain T30, and the sterile artificial diet. The Enterococcus sp. strain was isolated and characterized from the healthy larvae midgut of the Asian corn borer. An infection study of the Asian corn borer larvae using Enterococcus sp. ACB-1 revealed that a correlation existed between the increased Enterococcus community in the larval midgut and larval mortality. These results demonstrated that the transgenic Trichoderma strain could affect the composition of the midgut bacterial community. The change of the midgut bacterial community might be viewed as one of the factors resulting in the increased mortality of the Asian corn borer larvae.